Corporal Punishment and Discipline: What Teachers of Secondary Schools of Kolkata and Durgapur of West Bengal Speak - Mondal, Naba K; Prasad, Sunayna (JOURNAL OF INDIAN EDUCATION, 2012)
Corporal punishment is often justified as a necessary mean to create classroom discipline. This paper provides the views of government and private school teachers regarding use and role of corporal punishment maintaining discipline. Results revealed that the classroom condition play vital role in causing indiscipline among students and teachers take the path of corporal punishment to maintain discipline. Corporal punishment is favoured and supported by majority of teachers for disciplinary status. Use of corporal punishment does not depend upon gender of the child. Home and society in which a child grows has immense effect on his indisciplined behaviour.